PENGARUH STRATEGI PEMBELAJARAN ACTIVE LEARNING MODEL GIVING QUESTION AND GETTING ANSWER TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN FIQIH DI MI MIFTAHUL JINAN WONOAYU - Sufinatin Aisida (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2019)
Learning strategies have role which is very good in learning process in give birth  human Resources quality, this research study about influence learning strategies Active Learning Model Giving Question And Getting Answer to learning achievement student on subjects fiqih. The results of this study shows that that implementation influence Learning strategies Active Learning Model Giving Question And Getting Answer to learning achievement student on subjects fiqih to student achievement  in Fiqi subjects in MI Miftahul Jinan Wonoayu Sidoarjo. Well done with a very good category,this is based from prosentase results gained 90%  which value is are at vulnerable 85-100%. And influence Learning strategies Active Learning Model Giving Question And Getting Answer to learning achievement student on subjects fiqih to student achievement  in Fiqi subjects in MI Miftahul Jinan Wonoayu Sidoarjo this metter prosentase value Product Moment the value obtained “rxy” of 0,717.wich shows is influence sufficient.Learning strategies have role which is very good in learning process in give birth  human Resources quality, this research study about influence learning strategies Active Learning Model Giving Question And Getting Answer to learning achievement student on subjects fiqih. The results of this study shows that that implementation influence Learning strategies Active Learning Model Giving Question And Getting Answer to learning achievement student on subjects fiqih to student achievement  in Fiqi subjects in MI Miftahul Jinan Wonoayu Sidoarjo. Well done with a very good category,this is based from prosentase results gained 90%  which value is are at vulnerable 85-100%. And influence Learning strategies Active Learning Model Giving Question And Getting Answer to learning achievement student on subjects fiqih to student achievement  in Fiqi subjects in MI Miftahul Jinan Wonoayu Sidoarjo this metter prosentase value Product Moment the value obtained “rxy” of 0,717.wich shows is influence sufficient.